PERBANDINGAN AKUMULASI TABUNGAN PENSIUN PADA BERBAGAI TINGKAT INFLASI MENGGUNAKAN SIMULASI MONTE CARLO - Husni Johan, Arsyelina; Andriani, Rosa; Prafidya Romantica, Krishna (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
The inflation rate can diminish the value of savings, which impacts the adequacy of savings to meet long-term living needs. This inadequacy can be mitigated by investing in assets with optimal returns under various inflation conditions. Using a stochastic modeling approach, retirement savings accumulation can be projected through Monte Carlo simulation by generating random returns for various combinations and allocations of investment assets. The research findings show that inflation rates affect investment performance, as indicated by differences in investment returns and retirement savings accumulation across different inflation rate categories. The investment performance of the asset combination of deposits and stocks yields the highest savings accumulation in all inflation categories with average exceeding IDR 160 million. Through this study, it is expected that investors or retirees can choose the appropriate asset allocation to build optimal retirement savings.